What Makes Writing Academic Rethinking Theory for Practice - Molinari, Julia (Bloomsbury Academic, 2022)
This book argues that what makes writing academic emerges from socio-academic and historical practices rather than conventionalised stylistic, linguistic or syntactic forms. Using a critical realist lens, it re-imagines academic writings as 21st century open systems that change according to affordances perceived by writers. In so doing, the book offers opportunities for re-imagining how, which and whose knowledge emerges. Academic communication hinges on being able to write in certain forms but not others, which risks excluding knowledge that may lend itself to alternative forms of representation, including dialogues, chronicles, manifestos, blogs and comics. Moreover, because academic ability tends to be misleadingly conflated with writing ability, limiting how the academy writes to a relatively narrow set of forms (such as the essay or thesis), may be preventing a range of abilities from emerging. Standardised forms require abstracts, introductions, main bodies, and conclusions and are also predominantly monolingual and monomodal; this can narrow, distort or flatten epistemic representation and can lead to a range of epistemic losses and gains. Drawing on the history of academia, socio-semiotic research, integrational linguistics, and studies in multimodal and visual thinking, and presenting examples from a range of academic writers including students, the book proposes that academic writings be re-imagined as multimodal artefacts that harness a wider range of epistemic affordances.